Water use and yield of soybean under various irrigation regimes and severe water stress. Application of AquaCrop and SIMDualKc models - Giménez, Luis (2017)
Data relative to two soybean seasons, several irrigation scheduling treatments, including moderate and severe deficit irrigation, and rain-fed cropping were used to parameterize and assess the performance of models AquaCrop and SIMDualKc, the latter combined with the Stewart’s yield model. SIMDualKc applies the FAO56 dual crop coefficient approach for computing and partitioning evapotranspiration (ET) into actual crop transpiration (Tc act) and soil evaporation (Es), while AquaCrop uses an approach that depends on the canopy cover curve. The calibration-validations of models were performed by comparing observed and predicted soil water content (SWC) and grain yield. SIMDualKc showed good accuracy for SWC estimations, with normalized root mean square error (NRMSE) 7.6%. AquaCrop was less accurate, with NRMSE 9.2%. Differences between models regarding the water balance terms were notable, and the ET partition revealed a trend for under-estimation of Tc act by AquaCrop, mainly under severe water stress. Yield predictions with SIMDualKc-Stewart models produced NRMSE < 15% while predictions with AquaCrop resulted in NRMSE 23% due to under-estimation of Tc act, particularly for water stressed treatments. Results show the appropriateness of SIMDualKc to support irrigation scheduling and assessing impacts on yield when combined with Stewart’s model